An assessment of using variable blade pitch for moored ocean current turbine flight control. (April 2016) - VanZwieten, James H.; Pyakurel, Parakram; Ngo, Tri; Sultan, Cornel; Xiros, Nikolaos I.
Highlights: Harmonic individual blade pitch is used for controlling ocean current turbines. A representative ocean current turbine design is presented. Numerical prediction of turbine response to harmonic blade pitch control. Increased ocean current turbine farm power production. Abstract: This paper investigates the possibility of using active individual blade pitch control for positioning moored ocean current turbines within an array. Using a numerical simulation of a representative ocean current turbine it is shown that harmonic blade oscillations with amplitudes of 1.5° can be used to displace an ocean current turbine laterally by a distance equal to one rotor diameter, when the mooring cable length is approximately 30 times the diameter of the rotor blade. For current flow directions that would result in a downstream turbine operating in the wake of an upstream system at a distance of 10 diameters, this technique could be used to reduce the power loss of the downstream system from about 50% (caused by the reduced flow speed available in the turbine wake) to the 1.2% power loss associated with the suggested control approach.